2009
DOI: 10.1089/cap.2008.0081
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Application to Two Different Skin Sites on the Pharmacokinetics of Transdermal Methylphenidate in Pediatric Patients with Attention-Deficit/Hyperactivity Disorder

Abstract: MTS applied to both hip and scapular areas resulted in quantifiable plasma levels of d,l-MPH. Bioavailability of MPH from the same transdermal delivery system appears to differ substantially when applied to two different skin surfaces in young children but with similar overall skin effects assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…A comparison of two sites found that application of MTS to the hip resulted in a significantly greater C max than application to the scapula (33.8 ± 10.2 vs. 26.2 ± 11.2 ng/mL, p  = 0.01 hip vs. scapula) in boys and girls (aged 6–12 years) during a 16-h wear time [26]. The area under the curve from 0 to 16 h (AUC 0–16 ) was also greater with hip placement, although the t max was only slightly longer with hip placement.…”
Section: Transdermal Methylphenidate In Attention-deficit Hyperactivimentioning
confidence: 99%
“…A comparison of two sites found that application of MTS to the hip resulted in a significantly greater C max than application to the scapula (33.8 ± 10.2 vs. 26.2 ± 11.2 ng/mL, p  = 0.01 hip vs. scapula) in boys and girls (aged 6–12 years) during a 16-h wear time [26]. The area under the curve from 0 to 16 h (AUC 0–16 ) was also greater with hip placement, although the t max was only slightly longer with hip placement.…”
Section: Transdermal Methylphenidate In Attention-deficit Hyperactivimentioning
confidence: 99%
“…Transdermal methylphenidate bypasses the oral route entirely, and in short-term studies is associated with efficacy throughout the day, with improved family quality of life, and when carefully titrated, little effect on sleep [44-46]. Greater absorption of medication occurs when the patch is applied to the buttocks rather than to the subscapular area [47]. …”
Section: Adhd Treatmentsmentioning
confidence: 99%
“…[11] Reported results were obtained after daily application of methylphenidate transdermal system to the hip (each application lasting 9 hours). [11] Results of this trial are supplemented by data from trials in children aged 6-12 years with ADHD who received methylphenidate transdermal system, [12,13] and by data from the manufacturer's prescribing information. [11] Results of this trial are supplemented by data from trials in children aged 6-12 years with ADHD who received methylphenidate transdermal system, [12,13] and by data from the manufacturer's prescribing information.…”
Section: Pharmacokinetic Profilementioning
confidence: 99%
“…[11] Accumulation was seen with repeated application; the steady-state accumulation ratio for adolescents receiving methylphenidate transdermal system 10 mg for 28 days was 83% relative to a single application of methylphenidate transdermal system 10 mg. [11] An approximately dose-proportional increase in d-methylphenidate plasma trough concentrations was seen in adolescents receiving methylphenidate transdermal system 10-30 mg. [11] In adolescents receiving methylphenidate transdermal system, the plasma concentration-time profile of l-methylphenidate approximated that of d-methylphenidate, although l-methylphenidate concentrations were about half those of d-methylphenidate. [12] In children with ADHD, the bioavailability of d,l-methylphenidate was »31% greater following a single 16-hour application of methylphenidate transdermal system (patch size of 25 cm 2 ) to the hip versus the scapula. [12] In children with ADHD, the bioavailability of d,l-methylphenidate was »31% greater following a single 16-hour application of methylphenidate transdermal system (patch size of 25 cm 2 ) to the hip versus the scapula.…”
Section: Pharmacokinetic Profilementioning
confidence: 99%
See 1 more Smart Citation